Development of healthy snacks enriched with microencapsulated organic propolis: evaluation of biological properties, bioaccessibility, cellular transport, and prebiotic action - Saliba, Ana Sofia Martelli Chaib (2025)
Brazil is one of the worlds leading producers and exporters of Apis mellifera propolis, known for its broad spectrum of biological activities. Although legally classified as a food in several countries, its consumption remains largely limited to aqueous or hydroalcoholic extracts, which restricts its application in functional foods. Organic propolis from conservation areas in southern Paraná and northern Santa Catarina stands out for its mild sensory profile, absence of pesticide and heavy metal residues, and high antioxidant activity. This translational study aimed to evaluate different encapsulation strategies for organic propolis, with the goal of incorporating it into a fruit-based functional food, the fruit leather. Three microencapsulation approaches were tested: spray-drying with gum arabic (GA+OPE), spray-chilling with vegetable fat (VF+OPE), and a combination of both matrices via spray-drying (GA+VF+OPE). The particles were evaluated for morphology, chemical composition, antioxidant capacity, anti-inflammatory activity, stability during simulated gastrointestinal digestion, and epithelial transport in Caco-2 cells. The GA+VF+OPE formulation showed the best performance, with significantly higher antioxidant activity against peroxyl and hypochlorous acid radicals, along with pronounced anti-inflammatory effects. At a concentration of 100 g/mL, this formulation reduced NF-B transcription factor activation by 28% and TNF- secretion by 53% in LPS-stimulated RAW 264.7 macrophages. LC-ESI-QTOF-MS analysis confirmed the preservation of bioactive phenolic compounds after digestion and epithelial transport. Subsequently, both encapsulated (GA+VF+OPE) and non-encapsulated propolis were incorporated into strawberry and banana fruit leathers. In vitro assays demonstrated enhanced radical scavenging activity (ROO, OH, and HOCl) and a reduction in inflammatory markers. The bioaccessible fraction of the bar containing encapsulated propolis reduced (p < 0.05) NF-B activation by 86% and TNF- secretion by 90%, while the non-encapsulated extract reduced these markers by 89% and 81%, respectively. The chemokine CXCL2/MIP-2 was also reduced (p < 0.05) by over 95% in both formulations. In vivo studies using C57BL/6 mice revealed the prebiotic potential of the formulations. Metagenomic analysis of fecal samples showed positive modulation of the gut microbiota, with an increased relative abundance of beneficial genera such as Lactobacillus and Lachnospiraceae, especially in groups treated with fruit leathers containing the encapsulated propolis. Overall, the results demonstrate that microencapsulation using the GA+VF+OPE formulation is effective in protecting and delivering the bioactive compounds of organic propolis, promoting antioxidant, anti-inflammatory, and gut microbiota-modulating effects. Incorporating these particles into fruit-based functional foods represents a promising strategy for the development of functional products with potential industrial applications